2020
DOI: 10.3390/app10186418
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Lead from Water Solution by Reusable Magnetic Adsorbent Incorporating Selective Lead-Binding Peptide

Abstract: As a reusable adsorbent to remove lead from water, a peptide-based magnetic adsorbent incorporating lead-binding peptide was constructed. First, a 7-mer lead-binding peptide (TNTLSNN) was covalently bonded onto the surface of a magnetic bead. Compared to the adsorption capacity of a bare magnetic bead (4.0 mg lead/g bead), the peptide-linked bead exhibited a capacity more than eight times higher than that of a bare bead (34.1 mg lead/g bead). The regenerated peptide bead, by desorbing the lead from the bead wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The complete removal of the pesticide in the wash-step was demonstrated by analyzing the infrared spectra of the PCL mats and UV–vis spectrophotometry of the solution before and after the rising; see Figure S11a, b. This reactivation method is less aggressive and faster in comparison with others found in the literature, such as exposure to high temperatures, , centrifugation , or acids . Interestingly, in Figure c, the SEM image of the samples after the five cycles, which comprise a total of 20 days, revealed that the inner morphology of the samples remained unspoilt.…”
Section: Resultsmentioning
confidence: 93%
“…The complete removal of the pesticide in the wash-step was demonstrated by analyzing the infrared spectra of the PCL mats and UV–vis spectrophotometry of the solution before and after the rising; see Figure S11a, b. This reactivation method is less aggressive and faster in comparison with others found in the literature, such as exposure to high temperatures, , centrifugation , or acids . Interestingly, in Figure c, the SEM image of the samples after the five cycles, which comprise a total of 20 days, revealed that the inner morphology of the samples remained unspoilt.…”
Section: Resultsmentioning
confidence: 93%
“…However, some of the major challenges facing such implementation from producing optimum efficiencies are high materials and implementation costs, scarcity of raw materials, materials limitation, lack or insufficient power supply, secondary waste management, etc (Ahmed et al, 2022;Kriss et al, 2021;Sharma and Bhattacharya, 2017). Adsorption is one of the widely accepted methods that can easily be modelled towards the achievement of excellent efficiency through materials selection, eco-friendly practices and limited input of resources (Wang et al, 2020;Xu and Yoo, 2020). There are different materials suitable as adsorbents for the removal of lead (II) from an aqueous solution such as plant and animal materials (Maftouh, et al, 2023), inorganic materials (Chowdhury et al, 2022), organic and inorganic polymers (Ngamsurach et al,) and synthetic materials (Ahmad et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the presence of abundant functional groups such as hydroxyl groups, thiol groups, and carboxyl groups as adsorption sites, along with diverse secondary structures, a series of peptides has been studied for their binding to various metallic materials, including metal oxides, metal sulfides, and metals [ 17 , 18 ]. Moreover, some specifically designed peptides demonstrate a selective affinity for particular metal ions, which can serve as effective metal-binding moieties in aqueous solutions and promote selective metal ion adsorption [ 19 ].…”
Section: Introductionmentioning
confidence: 99%